2011
DOI: 10.7589/0090-3558-47.4.860
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Seasonal Prevalence of Plasmodium Spp. In a Rare Endemic New Zealand Passerine (Tieke or Saddleback, Philesturnus Carunculatus)

Abstract: ABSTRACT:The conservation and management of Saddlebacks (Philesturnus carunculatus) and other New Zealand birds, currently relies on the translocation of individuals to predator-free sites. Avian malaria has been identified as one of the diseases to be tested for prior to translocations in New Zealand, with the aim of translocating disease-free individuals. We describe avian malaria lineages and their seasonal prevalence in [2007][2008] in Saddlebacks from Mokoia Island, a source of birds for translocations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…It was also interesting to note that the globally widespread P. elongatum was by far the most common malaria parasite encountered in silvereyes in this study (n = 20). This finding is in accordance with previous studies in New Zealand, which have demonstrated the presence of P. elongatum in a wide range of native species and its ubiquitous distribution throughout the country (Baillie and Brunton 2011;Castro et al 2011;Ewen et al 2012;Howe et al 2012).…”
Section: Discussionsupporting
confidence: 83%
“…It was also interesting to note that the globally widespread P. elongatum was by far the most common malaria parasite encountered in silvereyes in this study (n = 20). This finding is in accordance with previous studies in New Zealand, which have demonstrated the presence of P. elongatum in a wide range of native species and its ubiquitous distribution throughout the country (Baillie and Brunton 2011;Castro et al 2011;Ewen et al 2012;Howe et al 2012).…”
Section: Discussionsupporting
confidence: 83%
“…This parasite is able to develop in non-adapted birds such as brown kiwi and different species of penguins Howe et al, 2012). Recent studies reveal the number of records of P. elongatum in introduced and endemic New Zealand birds (Alley et al, 2010;Castro et al, 2011;Baillie et al, 2012;Howe et al, 2012;Clark et al, 2014;Schoener et al, 2014). The impact of avian malaria on native New Zealand birds is well illustrated by two cases in which 60% of New Zealand dotterels, Charadrius obscurus, and 80% of native mohua, Mohoua ochrocephala, were killed by Plasmodium spp.…”
Section: Introductionmentioning
confidence: 96%
“…Plasmodium elongatum is of particular importance due to its pathogenicity in both wild and captive birds Alley et al, 2010;Castro et al, 2011;Howe et al, 2012). This parasite is able to develop in non-adapted birds such as brown kiwi and different species of penguins Howe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain species of birds, such as canaries, penguins, ducks, pigeons, raptors, and domestic poultry, are highly susceptible to avian malaria, whereas other species of birds seem to be asymptomatic carriers of the parasite and do not develop the clinical disease. 27 In general, the presence of most blood parasites in wild birds has no effect on the health of the bird, although combined infections with Haemoproteus and Leukocytozoon can produce a fatal anemia. 28,29 Birds may be infected with a single blood parasite, or may have mixed infections based on examination of stained blood films.…”
Section: Blood Parasites Of Birdsmentioning
confidence: 99%